A 25/28 GHz Modified π-shaped SIW-based Self-Diplexing Antenna with Low Frequency Ratio for 5G Applications - Kumar A.; Singh A.K.; Kumar M. (My University, 2025)
In this paper, a compact substrate integrated waveguide (SIW) based self-diplexing slot antenna for 25/28 GHz fifth generation (5G) applications is presented. The SIW cavity is loaded with a 7r-shaped asymmetric slot that produce two distinct frequency bands and hence, self-diplexing antenna (SDA) characteristics with low frequency-ratio. The placement of the slot is chosen in such a way that it helps in creating weak cross-coupling path between the excitation ports. The slight modification in the slots dimensions further improves the isolation (>30 dB) in both frequency bands. The simulated peak gain and radiation efficiency in both frequency bands are 8.64 dBi, 9.54 dBi and 98.18%, 96.73%, respectively. The front-to-back ratio (FTBR) of more than 22 dB in both frequency bands is achieved. © 2021 IEEE.